1997
DOI: 10.1007/bf01285560
|View full text |Cite
|
Sign up to set email alerts
|

High affinity [3H]imipramine and [3H]paroxetine binding sites in suicide brains

Abstract: Specific binding of [3H]imipramine and [3H]paroxetine was simultaneously examined in human brains (frontal cortex, temporal cortex, cingulate cortex, hypothalamus, hippocampus and amygdala) from 11 controls and 11 depressed suicide victims. A single saturable high affinity site was obtained for both radioligands. Age was not related to significant changes in [3H]imipramine and [3H]paroxetine binding parameters, which indicates the stability of the brain serotonergic system with increasing age. A major finding … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
2

Year Published

2002
2002
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 40 publications
0
7
0
2
Order By: Relevance
“…Some of these studies reported a reduction in frontal cortex SERT binding (Stanley et al, 1982;Arato et al, 1991;Laruelle et al, 1993;Arango et al, 1995), one an increase (Meyerson et al, 1982), and the remainder no difference when compared to controls (Arato et al, 1987;Arora and Meltzer, 1989;Lawrence et al, 1990aLawrence et al, , b, 1998Mann et al, 1996;Rosel et al, 1997Rosel et al, , 1998Bligh-Glover et al, 2000). One group failed to find SERT density alterations in the frontal cortex of violent suicides but did find a decrease in the hippocampus using [ 3 H]-imipramine, which was not confirmed using [ 3 H]-paroxetine in the same tissue samples (Rosel et al, 1997(Rosel et al, , 1998. Lawrence et al (1998) demonstrated a decrease in SERT binding in the putamen of nonviolent suicides with no differences in the binding of violent suicides.…”
Section: Sert In the Brainmentioning
confidence: 99%
See 2 more Smart Citations
“…Some of these studies reported a reduction in frontal cortex SERT binding (Stanley et al, 1982;Arato et al, 1991;Laruelle et al, 1993;Arango et al, 1995), one an increase (Meyerson et al, 1982), and the remainder no difference when compared to controls (Arato et al, 1987;Arora and Meltzer, 1989;Lawrence et al, 1990aLawrence et al, , b, 1998Mann et al, 1996;Rosel et al, 1997Rosel et al, , 1998Bligh-Glover et al, 2000). One group failed to find SERT density alterations in the frontal cortex of violent suicides but did find a decrease in the hippocampus using [ 3 H]-imipramine, which was not confirmed using [ 3 H]-paroxetine in the same tissue samples (Rosel et al, 1997(Rosel et al, , 1998. Lawrence et al (1998) demonstrated a decrease in SERT binding in the putamen of nonviolent suicides with no differences in the binding of violent suicides.…”
Section: Sert In the Brainmentioning
confidence: 99%
“…Although many of the studies of SERT binding in postmortem brain tissue from suicide completers have examined both violent and nonviolent suicides, several have used violent completers exclusively or have subdivided the suicide group based on the use of violent means (Meyerson et al, 1982;Stanley et al, 1982;Arato et al, 1987Arato et al, , 1991Arora and Meltzer, 1989;Lawrence et al, 1990aLawrence et al, , b, 1998Rosel et al, 1997Rosel et al, , 1998Bligh-Glover et al, 2000). Other studies included only one or two suicide victims who had died by nonviolent methods, while the majority of subjects used violent means (Laruelle et al, 1993;Arango et al, 1995;Mann et al, 1996).…”
Section: Sert In the Brainmentioning
confidence: 99%
See 1 more Smart Citation
“…Most studies report a decrease (95-98) or no change (99) in 5-HTT binding affinity in the hippocampus and prefrontal cortex, although an increase has also been reported (100). Fewer neurons express the serotonin transporter in the raphe nuclei of suicide victims.…”
Section: Neurotransmitter Systems Implicated In Suicidementioning
confidence: 99%
“…Decreased activity in the serotonergic pathways from midbrain raphe to forebrain regions has been associated with a high risk of suicide and with impulsive, aggressive behaviour [4][5][6][7]. Studies in postmortem brain tissue from suicide victims showed a presynaptic serotonergic deficit [8][9][10][11][12] resulting in compensatory upregulation of postsynaptic 5-HT receptors (5-HT 1A and 5-HT 2A ) in the prefrontal cortex [13][14][15][16][17][18][19][20]. In psychiatric patients with affective disorders and mood disorders decreased 5-HT concentrations in the cerebrospinal fluid (CSF) or specific brain sections were reported, especially in acute depressive phases.…”
Section: Introductionmentioning
confidence: 99%